The Proximate Chemical Composition of Barks of Some Indian Trees: Part I - Karnik, M. G.; Bhatia, Kuldip; Dobhal, P. C. (Indian Forester, 1970)
The barks of the woods of Tectona grandis, Adina cordifolia, Anogeissus latifolia, Lagerstroemia parviflora, Cleistanthus callinus, Pterocarpus marsupium and Bosvellia serrata received from the Forest Utilisation Officer, Maharashtra State were analysed for tannins, cold water solubility, hot water solubility, ash, peat, ether extractives, alcohol benzene extract, pentosans,lignin and chlorite holocellulose content following standard methods. The barks were also tested qualitatively for starch and alkaloids. The results are reported in the article.